2017
DOI: 10.1186/s40164-017-0070-9
|View full text |Cite
|
Sign up to set email alerts
|

Advances of CD19-directed chimeric antigen receptor-modified T cells in refractory/relapsed acute lymphoblastic leukemia

Abstract: Refractory/relapsed B-cell acute lymphoblastic leukemia remains to be a significant cause of cancer-associated morbidity and mortality for children and adults. Developing novel and effective molecular-targeted approaches is thus a major priority. Chimeric antigen receptor-modified T cell (CAR-T) therapy, as one of the most promising targeted immunotherapies, has drawn extensive attention and resulted in multiple applications. According to published studies, CD19-directed CAR-T cells (CD19 CAR-T) can reach a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 48 publications
1
42
0
6
Order By: Relevance
“…The adoptive infusion of CD19‐targeted CAR‐T cells showed promising treatment effects for R/RB‐ALL. Despite in vivo CAR‐T cell expansion and the achievement of CR, relapses still occur after treatmentin some patients with CD19 + leukemia cells as a result of CAR‐T loss or inhibitory tumor microenvironment . Transgene‐specific immune responses were demonstrated to limit the in vivo persistence of adoptively transferred herpes‐simplex‐virus thymidine‐kinase modified donor T cells, and a recent study showed that some patients treated with anti‐CD19 or anti‐CAIX CAR‐T cells developed an immune response specific for epitopes in murine scFv and rendered subsequent T‐cell infusions ineffective .…”
Section: Discussionmentioning
confidence: 99%
“…The adoptive infusion of CD19‐targeted CAR‐T cells showed promising treatment effects for R/RB‐ALL. Despite in vivo CAR‐T cell expansion and the achievement of CR, relapses still occur after treatmentin some patients with CD19 + leukemia cells as a result of CAR‐T loss or inhibitory tumor microenvironment . Transgene‐specific immune responses were demonstrated to limit the in vivo persistence of adoptively transferred herpes‐simplex‐virus thymidine‐kinase modified donor T cells, and a recent study showed that some patients treated with anti‐CD19 or anti‐CAIX CAR‐T cells developed an immune response specific for epitopes in murine scFv and rendered subsequent T‐cell infusions ineffective .…”
Section: Discussionmentioning
confidence: 99%
“…Использование анти-генсвязывающего домена анти-CD19 в составе CAR для адоптивной иммунотерапии позволило получить многообещающие результаты при рецидивах и реф-рактерных В-клеточных неоплазиях [46].…”
Section: Discussionunclassified
“…Таким образом, анализ in vitro показал избирательность цитотоксического эффекта CAR T-лимфоцитов, их способность к продукции цито-кинов и выраженную пролиферативную активность как при сокультивировании с клетками-мишенями, так и при присутствии в среде культивирования целе-вого антигена. Несмотря на впечатляющие результаты CAR-T-терапии, полученные в клинических исследованиях [46,49], крайне высокая стоимость [50] производства CAR T-лимфоцитов является серьезным препятствием на пути ее широкого применения в клинической прак-тике. Именно поэтому актуальность разработки тех-нологии для получения универсальных аллогенных CAR-T (позволяющей существенно снизить стоимость терапии) чрезвычайно высока.…”
Section: Discussionunclassified
“…Relapse is related to the short duration or abnormal functions of CAR T-cells. The mechanisms of action may involve CD19 gene deletion or mutation, defects of gene transcription, transformation of leukemia cell type, and/or CD19negative clonal evolution [92]. The other type of relapse, involving cases in which CAR Tcells did not persist, is less frequent in patient treated with CTL-019 infusion.…”
Section: Expert Opinionmentioning
confidence: 98%